Determination of Some Trace Elements in Buffalo’s Milk in Tanjaro Area-Sulaimani-Iraq - Khasraw, Bawan Mohammad Najeeb; Mahmood, Karzan Tofiq (Sulaimani Journal for Pure and Applied Sciences, 2018)
Buffalo’s raw milk subjected to various physical, chemical and biological pollutants due to produce, transporting and marketing processes. The current study was designed to assess the level of some trace elements in buffalo's raw milk. Milk samples were collected from 2 fields located on Tanjaro River during 1 years, the highest mean value of Pb, Cd, Cr, Cu and Zn were 0.075, 0.005, 0.010, 0.126 and 0.723 mg.kg-1 were recorded, respectively. The data showed that the most polluted season for Pb was during autumn with the average of 0.051 mg.kg-1, while the most polluted season for Cd and Cu was the end summer with the average value 0.004 and 0.103 mg.kg-1 respectively, but for the both trace elements Cr and Zn the spring season is the most polluted season with the average of 0.006 and 0.669 mg.kg-1 respectively.
Keywords: Buffalo Raw milk Trace elements